WEAKLY UNIQUE FACTORIZATION MODULES - Oral, Kursat Hakan; Tekir, Unsal; Agargun, Ahmet Goksel (TAMKANG UNIV, 2010)
In this work we give the definition of weakly prime element of a module. Therefore we give a new definition of factorization in a module, which is called weakly factorization. So we call a module weakly unique factorization module if all elements have a weakly factorization which is unique. We give the relation between weakly prime elements and weakly prime submodules. Then we characterize such weakly unique factorization modules.
Keywords: Weakly prime element; weakly prime submodule; factorization; Mathematics